Desenvolvimento de protocolos para seleção de espécies e avaliação de funções ecológicas e serviços ecossistêmicos - Francisco, Bruno dos Santos (2023)
Economic activity, quality of life and cohesion of human societies depend profoundly and irremediably on the services generated by ecosystems, making it relevant to study the dynamics of generation of environmental services and their interactions with human and functional variables. For this we can use tools that help us measure and compare environments, species and ecosystems. In this work we used different protocols to evaluate seedling production, different ecological restoration techniques and different ecosystems in mountain areas. In chapter two, we created and used a protocol for the production of seedlings in a nursery with a more ecological approach, based on attributes chosen based on a bibliographical review. In chapter three, we used the ecological functionality monitoring protocol to evaluate three restoration techniques, one of which is called strip planting, a new technique in the literature that mixes planting seedlings and conducting natural regeneration. In chapter four, we created and applied the ecosystem service assessment protocol in a mountain area in northern Portugal. The adoption of sustainable management practices and the application of systemic data analysis by protocols will serve to improve methods of restoration and monitoring of ecological processes and contribute to the proposition of public policies that value the environmental services provided by different ecosystems